2018
DOI: 10.3389/fpsyg.2018.00663
|View full text |Cite
|
Sign up to set email alerts
|

Motivated Shield From Chronic Noise Environment: Moderation of the Relationship Between Noise Sensitivity and Work Wellbeing by Need for Closure

Abstract: Several studies have underlined how chronic exposure to environmental noise may have negative effects on performance, wellbeing, and social relations. The present study (N = 90 employees of a motor factory who are chronically exposed to environmental noise) investigated whether the negative effects of chronic exposure of noise-sensitive individuals to noise in the workplace may be moderated by the need for cognitive closure (i.e., an epistemic tendency to reduce uncertainty; NFCC, Kruglanski, 2004). As NFCC ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In humans, it has been reported that chronic and low intensity noise, including aircraft noise, can cause disturbances of activity, sleep, and communication, leading to emotional reactions such as annoyance and stress (Golbidi et al., 2018; Olaosun et al., 2009; Yoon et al., 2014), as well as reading comprehension, memory, and concentration difficulties in children (Clark et al., 2012; Evans et al., 2001; Stansfeld & Clark, 2015; van Kempen et al., 2012) and an increase in the risk to cardiovascular and metabolic diseases (Livi et al., 2018; Münzel et al., 2014; Schmidt et al., 2013; Tamura et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, it has been reported that chronic and low intensity noise, including aircraft noise, can cause disturbances of activity, sleep, and communication, leading to emotional reactions such as annoyance and stress (Golbidi et al., 2018; Olaosun et al., 2009; Yoon et al., 2014), as well as reading comprehension, memory, and concentration difficulties in children (Clark et al., 2012; Evans et al., 2001; Stansfeld & Clark, 2015; van Kempen et al., 2012) and an increase in the risk to cardiovascular and metabolic diseases (Livi et al., 2018; Münzel et al., 2014; Schmidt et al., 2013; Tamura et al., 2012).…”
Section: Introductionmentioning
confidence: 99%